Novel Molecular Hybrids of N-Benzylpiperidine and 1,3,4-Oxadiazole as Multitargeted Therapeutics to Treat Alzheimer's Disease - Sharma P.; Tripathi A.; Tripathi P.N.; Singh S.S.; Singh S.P.; Shrivastava S.K. (My University, 2025)
Multitargeted hybrids of N-benzylpiperidine and substituted 5-phenyl-1,3,4-oxadiazoles were designed, synthesized, and evaluated against Alzheimer's disease (AD). Tested compounds exhibited moderate to excellent inhibition against human acetylcholinesterase (hAChE), butyrylcholinesterase (hBChE), and beta-secretase-1 (hBACE-1). The potential leads 6g and 10f exhibited balanced inhibitory profiles against all the targets, with a substantial displacement of propidium iodide from the peripheral anionic site of hAChE. Hybrids 6g and 10f also elicited favorable permeation across the blood-brain barrier and were devoid of neurotoxic liability toward SH-SY5Y neuroblastoma cells. Both leads remarkably disassembled Aβ aggregation in thioflavin T-based self- and AChE-induced experiments. Compounds 6g and 10f ameliorated scopolamine-induced cognitive dysfunctions in the Y-maze test. The ex vivo studies of rat brain homogenates established the reduced AChE levels and antioxidant activity of both compounds. Compound 6g also elicited noteworthy improvement in Aβ-induced cognitive dysfunctions in the Morris water maze test with downregulation in the expression of Aβ and BACE-1 proteins corroborated by Western blot and immunohistochemical analysis. The pharmacokinetic study showed excellent oral absorption characteristics of compound 6g. The in silico molecular docking and dynamics simulation studies of lead compounds affirmed their consensual binding interactions with PAS-AChE and aspartate dyad of BACE-1. © 2019 American Chemical Society.